Acute amebic appendicitis: Report of a rare case - Singh Naorem; Rifat Mannan A.A.S; Kahvic Mirza (Wolters Kluwer Medknow Publications, 2010)
Acute appendicitis of amebic origin is considered a rare cause of acute appendicitis. We report a case of amebic appendicitis presenting with fever, severe pain in the right lower quadrant of the abdomen and rebound tenderness. Lab investigations revealed neutrophilic leukocytosis. The patient underwent appendectomy. Histopathological examination revealed numerous Entameba histolytica trophozoites in the mucosa of the appendix. Acute appendicitis of amebic origin does not appear frequently. Appendicular amebiasis can give the clinical features of acute appendicitis and should be treated accordingly.